PRE-SERVICE TEACHERS’ SELF-REGULATED LEARNING STRATEGY, MOTIVATION, AND REVISION BEHAVIORS IN EFL ACADEMIC WRITING - Nabhan, Salim (Jurnal Pendidikan Bahasa, 2019)
The present study explored pre-service teachers’ self-regulated learning strategy and motivation in EFL academic writing. A further aim of the study is to investigate the relationship between their self-regulated learning strategy and motivation as well as to explore the revision behaviors in English academic writing. A questionnaire was administered to 56 pre-service teachers (PST) majoring English language education. The questionnaire covered 16 items of questions regarding self-regulated learning strategy comprising environmental process, behavioral process, and personal process, as well as motivation. PSTs’ revisions of academic writing were also assessed using writing revision categories to identify their revision behaviors. Descriptive analyses indicated that participants were moderate to high in their self-regulated learning strategy and motivation toward their writing activities. Furthermore, the result showed that despite the fact that self-regulated learning strategy in the aspect of environmental strategy and personal strategy did not significantly correlate with motivation, behavioral strategy significantly correlated with motivation. In addition to this, among the revision categories, the aspects of organization, citation, mechanics, language use, and references were the most common categories of revisions, while content and format were the least ones. The study might have implication on the PST’s EFL academic writing instruction. Keywords: self-regulated learning strategy, motivation, revision, EFL academic writing